TRANSLITERATION FROM LATIN INTO BALINESE SCRIPT (AKSARABALI)USING COMPUTERIZED PROGRAM OF BALI SIMBAR - Paramarta, I Ketut; Mbete, Aron Meko; Putra Yadnya, Ida Bagus; Putra, A.A. Putu (e-Journal of Linguistics; Vol. 9 Januari 2015 No. 1)
The process of transliteration(Latin-Balinese script) by using a computerized program of Bali Simbar is a noble step to preserve the existence of Balinese script from the domination of the written tradition with Latin letters. The utilization of Bali Simbar program in transliteration process has proved to have many advantages. First, the result of transliteration is not just a paper printout but canbe stored in digital soft copy form that does not require a large space, can be duplicated, and persist for a long time. Second, the process ofLatin-Balinese text transliteration by utilizing BaliSimbar program is much faster than manual transliteration. Third, the cost needed in the process of Latin-Balinese transliteration of satua is very little because it only requires a software program of Bali Simbar and computer (personal computer/PC, laptop, or notebook).   This study was focused on the transliteration of ten satua text from Gedong Kirtya Singaraja Museum collection performed by 4th semester students of Balinese  Language Education  Department of Undiksha.
Keywords: Transliteration, Latin letters, Balinese letters, computerized program of Bali Simbar